Numerical modelling of RC beams with bamboo reinforcement using finite element analysis (ANSYS) - Nur Afifah, Abdul Rahim (2018)
This research aims to investigate the behavior of reinforced concrete beams with partially and fully bamboo reinforcement. The objective of the research was to determine the geometrical properties of the element, to determine the behavior of solid RC beams and RC beams with partially and fully bamboo reinforcement in terms of load-deflection and crack pattern in finite element analysis. The finite element analysis results were validated with the experiment results. A total of three beams with a dimension of 120 x 300 mm with a length of 1600 mm were modeled as simplysupported beams in a three dimensional analysis using ANSYS. The types of beam modelled include solid beam (without reinforcement, partial reinforcement and fully reinforcement). Here a nonlinear finite element analysis is carried out in order to evaluate the performance of bamboo as reinforcement in concrete beam. The numerical modelling was conducted on control beam, partial bamboo replacement and fully replaced with bamboo as reinforcement. In this research, the reinforcement bars were modeled as 10 mm diameter bar for top and bottom reinforcement as well as 6 mm diameter stirrups with spacing of 300 mm center to center. From the finite element analysis results, the ultimate load for control beam was found to be 58.15 kN. The load for BR was 48.46 kN which is only 78% of the load of CB whereas the sample BSR obtained the load of 17.78 kN which is about 64% lower than BR and only achieved 31% compared to CB. The ultimate load for control beams was show that the failure loads for CB, BR, and BSR are 58.18kN, 48.46kN and 17.78kN with deflections of 38.67 mm, 19.98 mm and 10.89 mm respectively. In the end of the testing, it can be concluded that bamboo can be used to replace steel reinforcement in reinforced concrete beam. This application can be used in small structures of buildings structures in order to reduce the consumption of steel.